Rancang Bangun Model Lengan Infus Elvina Asnaty (EA) dalam Praktik Pemasangan Infus pada Mahasiswa Keperawatan Poltekkes Kemenkes Riau - Elvina Asnaty; Magdalena Magdalena; Melly Melly (Universitas Batanghari Jambi, 2022)
The infusion practice is one competence aspect from test nurse where a nurse have required ability in the infusion practice precisely and according to prosedur. One the factor influence ability in infusion practice is done during the educational institution. The infusion practice done in the laboratory using model media infus arm manufacturer. The infusion arm model was damaged impact on the infusion practice is not optimal result expected competence is not achieved so look for another alternative way with EA arm model design of using EA arm model design in infusion practice of nursing student in Poltekkes Kemenkes Riau. The research is purpose knowing the arm alternative media infusion practice other than media infus arm manufacturer and alternative media knowing between media manufacturer. This research was conducted in the Poltekkes Kemenkes Riau laboratory at 2021 which was tested by 3 lecturers of the medical surgical nursing team, 2 nursing laboratory staff and 15 nursing students using quantitative research with experimental research methods with a design quasi experimental sample using probability sampling technique with the type of proportionate stratified random sampling. The research was conducted using independent t test with normal and homogeneous data distribution. This shows that there is a difference between the manufacturer's infusion arm model and the EA infusion arm model. The research is output resulted in EA infusion arm model alternative media at infusion practice in addition to the manufacturer's infusion arm model and it can be seen the difference between the manufacturer's infusion arm model and the EA infusion arm model that can be used by nursing students.